Deregulation of PI3K/Akt/mTOR Signaling Pathways by Isoflavones and its Implication in Cancer Treatment - Ahmad, Aamir; Biersack, Bernhard; Li, Yiwei; Kong, Dejuan; Bao, Bin; Schobert, Rainer; B. Padhye, Subhash; H. Sarkar, Fazlul (Anti-Cancer Agents in Medicinal Chemistry, 2013)
Cancer remains a difficult disease to manage because of the deregulation of numerous signaling pathways that are associated with its development and progression. One such pathway is the phosphoinositide 3-kinase (PI3K) – protein kinase B (Akt) - mammalian target of rapamycin (mTOR) signaling network, which is known to be associated with poor prognosis in many human cancers. Targeted inhibition of this signaling network in vitro, in vivo and in clinics has suggested this to be an effective strategy for the inhibition of cancer cells’ proliferation and metastases. Towards this end, the use of natural agents for therapeutic intervention has attracted renewed interest because of their non-toxic effects as well as their ability to modulate multiple pathways. Investigations involving isoflavones have suggested a potent anticancer activity of these compounds against multiple factors in the PI3K/Akt/mTOR pathway. In addition to their use as therapeutic agents against various cancers, there is evidence to support the role of isoflavones in potentiation of radiation therapy as well as the anticancer action of other conventional therapeutic drugs. In this review article, we discuss our current understanding of the regulation of PI3K/Akt/mTOR signaling pathways by isoflavones, which could be responsible for their observed in vitro and in vivo activity against human cancers.
Keywords: sensitization